Pengaruh Waktu Penyangraian Terhadap Karakteristik Fisikokimia Kopi Bubuk Robusta Menggunakan Mesin Roasting Elektrik - Darajat, Aditya; Rifqi, Muhammad; Nurlaela, Raden Siti (JURNAL AGROINDUSTRI HALAL, 2023)
The quality of coffee powder can be improved if the main stages of the roasting process can be carried out optimally. Hot air-type roasting machines with a combination of 10 minutes and a temperature of 200 C can produce high-quality coffee powder. Therefore, other research is needed using different types of roasting machines and coffee powder quality criteria based on standards set by the government. The electric roasting machine consists of a Teflon heating mat that is directly integrated with temperature-adjustable heating components and has an automatic stirrer. The study used a one-factor Complete Randomized Design (CRD) with four treatment levels and two repeats. The Roast time of robusta coffee beans at a temperature of 200 C with levels (10, 15, 20, and 25) minutes is factor A. The criteria for testing the quality of coffee powder produced by the electric roasting machine state (smell, color, taste) with normal test results, water content ranges from 1.47-5.29%, ash content ranges from 3.53-3.83%, coffee juice ranges from 24.1-25.6%, and caffeine ranges from 1.66-1.78%. Electric roasting machines at a temperature of 200 C and 10 minutes are the best combination of treatment because the ground coffee produced is quality. I am referring to SNI 01-3542-2004 criteria for criteria tested with the most optimal electrical energy efficiency